HHV8/EBV Coinfection Lymphoproliferative Disorder: Rare Entity with a Favorable Outcome. (9th February 2017) - Bacha, Dhouha; Chelly, Beya; Kilani, Houda; Charfi, Lamia; Douggaz, Amel; Chatti, Samia; Chelbi, Emna
Abstract : HHV8/EBV-associated germinotropic lymphoproliferative disorder (GLD) is a challenging diagnosis given its rarity, the particular clinical presentation, and the lack of expression of markers usually used in establishing hematopoietic lineage. We report a new case of HHV8/EBV GLD in an immunocompetent 78-year-old woman. The diagnosis was made in an incidentally discovered lymphadenopathy. Histological examination showed a nodular lymphoid proliferation centered by aggregates of atypical plasmablastic cells admixed with small lymphoid cells. Tumor cells were strongly positive with EMA, HHV8, LMP1, CD38, CD138, and kappa light chains. They were negative with common lymphoma-associated markers (CD20, CD3, CD15, CD30, CD10, and bcl2). In situ hybridization confirmed the monotypic kappa light chains and the EBV infection (EBER+). A polyclonal pattern of Ig gene rearrangement was detected by PCR analysis. In the adjacent lymph node parenchyma, some germinal centers mimicked Castleman disease. In this case, the differential diagnosis was discussed with an early stage of large B-cell lymphoma arising in HHV8-associated multicentric Castleman disease. The clinical presentation, the immunophenotype, and the molecular results helped to make the accurate diagnosis. Through the review of the nine previously reported cases in literature, we discuss the clinical and pathologic features and the differential diagnosis of HHV8/EBV GLD.